2015
DOI: 10.15302/j-fase-2015082
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose aerogels decorated with multi-walled carbon nanotubes: preparation, characterization, and application for electromagnetic interference shielding

Abstract: Electromagnetic wave pollution has attracted extensive attention because of its ability to affect the operation of electronic machinery and endanger human health. In this work, the environmentally-friendly hybrid aerogels consisting of cellulose and multi-walled carbon nanotubes (MWCNTs) were fabricated. The aerogels have a low bulk density of 58.17 mg$cm . The incorporation of MWCNTs leads to an improvement in the thermal stability. In addition, the aerogels show a high electromagnetic interference (EMI) SE t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…We draw attention to another study, which reported on a series of cellulose-derived carbon aerogels that were obtained by Li et al Their materials featured multi-walled carbon nanotubes (MWC-NTs) [124], graphene oxide (GO) [125], and goethite (␣-FeOOH) nanoneedles and nanoflowers [126], all of which showed good electrical conductivity and absorption-dominant EMI shielding effects. Among them, GO decorated cellulose aerogels had the best total EMI shielding ability SE total having the value of 58.4 dB at 8.2-12.4 GHz.…”
Section: Emi Shieldingmentioning
confidence: 99%
“…We draw attention to another study, which reported on a series of cellulose-derived carbon aerogels that were obtained by Li et al Their materials featured multi-walled carbon nanotubes (MWC-NTs) [124], graphene oxide (GO) [125], and goethite (␣-FeOOH) nanoneedles and nanoflowers [126], all of which showed good electrical conductivity and absorption-dominant EMI shielding effects. Among them, GO decorated cellulose aerogels had the best total EMI shielding ability SE total having the value of 58.4 dB at 8.2-12.4 GHz.…”
Section: Emi Shieldingmentioning
confidence: 99%
“…The preparation process of cellulose hydrogel (the precursor of cellulose aerogel) was described in previous reports [15,16] . The prepared cellulose hydrogel was immersed in a freshly prepared aqueous solution of FeSO 4 $7H 2 O and MnCl 2 $4H 2 O (40 mL) with the stoichiometric ratio of Mn:Fe of 1:2.…”
Section: Preparation Of Mnfe 2 O 4 /Camentioning
confidence: 99%
“…The development of methods for the production of nanosized carbon materials extends the possibilities for controlling the properties of such coatings by varying the nature and type of the carbon filler distribution in the composite matrices . Of great interest are aerogels based on carbon nanotubes, which, due to their low weight and effective interaction with electromagnetic radiation, are promising for use as protective screens . We have developed the original one‐step method for production of muliwalled carbon nanotube (MWCNT) aerogels via a catalytic chemical vapor deposition (CCVD) with a specially formed catalyst (Fe–Co/CaO) at 650–700 °C in C 2 H 4 /Ar feedstock .…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Of great interest are aerogels based on carbon nanotubes, which, due to their low weight and effective interaction with electromagnetic radiation, are promising for use as protective screens. [6,7] We have developed the original one-step method for production of muliwalled carbon nanotube (MWCNT) aerogels via a catalytic chemical vapor deposition (CCVD) with a specially formed catalyst (Fe-Co/CaO) at 650-700 C in C 2 H 4 /Ar feedstock. [8,9] According to electron microscopy data and adsorption measurements, the MWCNTaerogels obtained show the structure of a rigid sponge of tangled nanotubes (bulk density 40-80 mg cm À3 and SBET 70-100 m 2 g À1 ).…”
Section: Introductionmentioning
confidence: 99%